Kerk en kultuur by die vryheidsoekende Afrikaner van die 1ge eeu - "n historiese ondersoek - Pont, A. D. (Hervormde teologiese studies, 1996)
Church vis it vis culture among the republican Afrikaner of the 19th century - an historical investigation. In this study attention is given to the question of the correlation between and/or position of the church vis a vis culture among the republican Afrikaner of the 19th century. Initially attention is given to a workohle definition of church and culture and then, in the light of Calvinist theology, the relationship is discussed. Eventually the stated problem is discussed and the conclusion formulated that the culture of the Afrikaner was strongly influenced and directed by its theological viewpoints. A few conclusions are drawn.